Electrochemical Studies of As(III) Complexes of Tyrosine - Paliwal, M.K.; Gupta, O.D. (Asian Journal of Chemistry, 2010)
The polarographic determination of stability constants of of As(III) complexes of tyrosine at 300 K in various aqueous and non-aqueous media, have shown the formation of 1:1, 1:2 and 1:3 complexes. The values of overall stability constants of complexes have been calculated by DeFord and Hume's method which is further verified by Mihailov's method. The reduction process was found to be quasireversible and diffusion controlled involving three electrons transfer. It was found that the stability constants of As(III)-tyrosine system in non-aqueous medium are less than in aqueous medium.